Common and well‐documented HLA alleles: 2012 update to the CWD catalogue. Issue 4 (20th March 2013) - Mack, S. J.; Cano, P.; Hollenbach, J. A.; He, J.; Hurley, C. K.; Middleton, D.; Moraes, M. E.; Pereira, S. E.; Kempenich, J. H.; Reed, E. F.; Setterholm, M.; Smith, A. G.; et al.
Abstract We have updated the catalogue of common and well‐documented (CWD) human leukocyte antigen (HLA) alleles to reflect current understanding of the prevalence of specific allele sequences. The original CWD catalogue designated 721 alleles at the HLA‐A, ‐B, ‐C, ‐DRB1, ‐DRB3/4/5, ‐DQA1, ‐DQB1, and ‐DPB1 loci in IMGT (IMmunoGeneTics)/HLA Database release 2.15.0 as being CWD. The updated CWD catalogue designates 1122 alleles at the HLA‐A, ‐B, ‐C, ‐DRB1, ‐DRB3/4/5, ‐DQA1, ‐DQB1, ‐DPA1 and ‐DPB1 loci as being CWD, and represents 14.3% of the HLA alleles in IMGT/HLA Database release 3.9.0. In particular, we identified 415 of these alleles as being 'common' (having known frequencies) and 707 as being 'well‐documented' on the basis of 140, 000 sequence‐based typing observations and available HLA haplotype data. Using these allele prevalence data, we have also assigned CWD status to specific G and P designations. We identified 147/151 G groups and 290/415 P groups as being CWD. The CWD catalogue will be updated on a regular basis moving forward, and will incorporate changes to the IMGT/HLA Database as well as empirical data from the histocompatibility and immunogenetics community. This version 2.0.0 of the CWD catalogue is available online at cwd.immunogenomics.org, and will be integrated into the Allele Frequencies Net Database, the IMGT/HLA Database and National Marrow Donor Program's bioinformatics web pages.